The Influence of Work Discipline and Career Development on Employee Performance at PT Astra Isuzu Palembang - M. Arman Derhawan; Hamid Halin; Fauziah Afriyani (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of Work Discipline and Career Development on Employee Performance at PT Astra Isuzu Palembang. The data used are primary data and secondary data. Data collection techniques are questionnaires, documentation and observation. The analysis method used is quantitative method. So that researchers take the entire population, namely employees totaling 54 people. The instrument used in this research is a questionnaire. This study uses a descriptive correlation method with the aim of providing an overview of the effect of Work Discipline and Career Development on Employee Performance of PT Astra Isuzu Palembang. Based on the data analysis conducted, it shows that the significant influence of variable X1 (work discipline) with variable X2 (career development) with variable Y (employee performance). Thus the results of the study can be concluded that the research hypothesis that there is a positive influence on Work Discipline and Career Development on Employee Performance of PT Astra Isuzu Palembang, can be tested or accepted.